The performance of an otto cycle Bi-fuel engine with natural gas direct injection - Barbosa, Cleiton Rubens Formiga; Da Silva, Mario Roberto [UNESP]; Celere, Samuel Washington (SAE International, 1996)
A bi-fuel engine using direct injection natural gas at low pressure was submitted to runs with full power in a foucaut dynamometer. The results obtained show a small decrease in power when the engine was fueled with natural gas when compared which carburated gasoline. Engine power data is compared, showing the factors which contribute to this reduction in power. Modifications to be made to minimize those losses are discussed © 1996 Society of Automotive Engineers, Inc.